A Qualitative Exploration of Romantic Partners' Motives for and Content of Communication with Friends Following Negative Relational Events. Issue 3 (26th May 2016) - Vallade, Jessalyn I.; Dillow, Megan R.; Myers, Scott A.
Abstract : The purpose of this study was to explore young adults' motives for and content of extradyadic interactions with friends following a negative relational event in a romantic relationship. Focus group discussions with young adults revealed the following partner motives: improving affect, managing uncertainty, obtaining clarity, and entertainment. In turn, friends were motivated by issues of honesty, friendship quality, and a desire to protect or comfort their friend. Both partners and friends discussed the use of a variety of negative, neutral, and positive message content. Results provide an exploratory look at extradyadic interactions that may have important implications for relationship functioning.